Cuticle alkanes of honeybee larvae mediate arrestment of bee parasite Varroa jacobsoni - Rickli, M.; Diehl, Peter-Allan; Guerin, Patrick (My University, 1994)
The ectoparasitic mite Varroa jacobsoni invades worker brood cells of the honeybee Apis mellifera during the last 20 hr before the cells are sealed with a wax cap. Cuticle extracts of 8-day-old worker honeybee larvae occupying such brood cells have an arrestment effect on the mite. The mites run for prolonged periods on the extract, systematically returning onto the stimulus after touching the borders of the treated area. Mites increase walking speed and path straightness in response to increasing doses of a nonpolar fraction of the cuticle extract. Saturated straight-chain odd-numbered C19–C29 hydrocarbons were identified by thin-layer argentation chromatography and gas chromatography-mass spectrometry as the most active constituents, with branched alkanes also contributing to the arrestment effect of this active fraction. Analysis of the behavior responses to synthetic n-alkanes indicate that the response is probably based on a synergism between the different alkane components of the fraction rather than to an individual compound.
Keywords: Varroa jacobsoni; Acari; Varroidae; mite; Apis mellifera; Hymenoptera; Apidae; honeybee; chemoreception; host selection; cuticle; hydrocarbons; alkanes